Multicultural/Multiethnic Education: A Critical Approach to the Educational Doctorate in Leadership - Carlos Nevarez; Lori Johnson Santamaria (Adult Education Research Conference, 2010)
In the coming years, the community college will experience unprecedented turnover in its leadership, especially among its senior ranks (Shults, 2001; Weisman & Vaughan, 2001; 2006). Weisman & Vaughan (2006) note that 84 percent of community college Chief Executive Officers (CEOs) plan to retire by 2016. Primarily, the ‘impending’ leadership void is being created by educators who entered the community college in the 1960s and 1970s, and have served in these institutions for decades (Phillippe & Sullivan, 2005; Schults, 2001). On the verge of retirement, the presidential ranks are becoming progressively older. In 1996, the average age of a community college president was 54; in 2001, it had risen to 56. By 2006, the average age of a president had increased to 58 (Weisman & Vaughan, 2006). While the average age of a community college president is 58, Duree (2007) notes that 44 percent of presidents are between the ages of 60 and 69, supporting the assertion that administrator turnover is forthcoming.